Agricultura familiar e previdência social rural: um estudo comparativo em quatro municípios gaúchos - Caldas, Nádia Velleda (2008)
The dissertation analyzes the importance of rural social welfare in the family farming. It approaches the effects of the universalization process of social welfare considering the changes resulting from the declaration of the 1988 Constitution. The study was developed based on a research performed in 238 rural settlements existing in four areas of study, corresponding to the micro-regions of Pelotas, Caxias do Sul, Frederico Westphalen and Cerro Largo, which are situated in the south, northeast, north and northwest of the geography on the Rio Grande do Sul respectively. The results show that the retirements and pensions are essentially important under the perspective of reducing inequalities. They represent an important income source for the families as well as for the economy of these settlements. The thesis that these resources are equally important to finance farm and cattle raising activities was proven under a considerable proportion (53%) in the investigated settlements as a whole. Besides, the research analyzed the evolution of the number and value of rural retirements and pensions for the years 2001 and 2006 in the four above mentioned micro-regions. If the decade of 1990 presents a substantial expansion in the system, the raising rates are reduced in the first six years of the XXI century for the number of retirement and pension holders in the State of Rio Grande do Sul. This data is important as it contradicts some opinions which insist upon the need to review the ways of granting benefits to the rural clientele, on account of the increase in the number of such holders, a trend which was not confirmed in the course of the present